New York City Politics : Governing Gotham - Berg, Bruce F. (Rutgers University Press, 2018)
Most experts consider economic development to be the dominant factor influencing urban politics. They point to the importance of the finance and real estate industries, the need to improve the tax base, and the push to create jobs. Bruce F. Berg maintains that there are three forces which are equally important in explaining New York City politics: economic development; the city's relationships with the state and federal governments, which influence taxation, revenue and public policy responsibilities; and New York City's racial and ethnic diversity, resulting in demands for more equitable representation and greater equity in the delivery of public goods and services. New York City Politics focuses on the impact of these three forces on the governance of New York City's political system including the need to promote democratic accountability, service delivery equity, as well as the maintenance of civil harmony. This second edition updates the discussion with examples from the Bloomberg and de Blasio administrations as well as current public policy issues including infrastructure, housing and homelessness, land use regulations, and education.
Keywords: Brooklyn (New York, N.Y.); Queens.; Gentrification.; Housing.; Political planning.; Rent control.; 911.; Brooklyn.; David Dinkins.; Empire State.; Jane Jacobs.; John Lindsay.; LaGuardia.; MTA.; Manhattan.; Mayor Bloomberg.; Mayor de Blasio.; New York City; New York; politics; government.; Penn Station.; Robert Moses.; Rudy Guiliani.; Staten Island.; The Bronx.; Wolrd Trade Center.; city council.; city.; development.; gentrification.; housing.; mayor.; municipal bureaucracy.; public policy.; rent control.; state.; subway.; Reines.; Embourgeoisement (Urbanisme); Politique publique.; Loyers -- Réglementation.; royalties (compensation); queens (people); POLITICAL SCIENCE -- General.; Gentrification; Housing; Political planning; Queens; Rent control; New York (State) -- New York -- Brooklyn; Electronic books.